Kekerasan Seksual dan Kebiri Kimia dalam Perspektif Undang-Undang Nomor 1 Tahun 2023 - Isyana Kurniasari Konoras (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The chemical castration penalty for perpetrators of sexual violence in Law Number 17 of 2016 concerning the Determination of Perppu Number 1 of 2016 concerning the Second Amendment to Law No. 23 of 2002 concerning Child Protection has been cancelled and declared invalid according to Law No. 1 of 2023 concerning the Criminal Code. This means that the President who approved, made, and signed it also revoked it and declared it invalid. There are two important aspects of the repeal of this provision, namely its relation to human rights and its relation to the provisions in Law No. 1 of 2023, which places it as a morality crime. From this point of view, the formation of statutory regulations receives an important place and attention. Community rejection of the provision of chemical castration is normal because there could be two victims. The study of the process of victimisation or multiple victims in criminal justice becomes complete in the context of how this process occurs in criminal justice institutions. Thus, law is not a text that exists in an empty space; law can only be meaningful if it is ‘spoken' in concrete events in society. The purpose of this writing is to describe legal dynamics through the formation of new laws, both those that are already in effect and those that will be implemented as anticipatory legal products in the future in the context of sexual violence. This must also consider the ability of law enforcement to respond to incidents related to sexual crimes through the media. electronic. This research is normative research. Normative research is a legal research method carried out by examining library materials. The results of this article conclude that the current regulations regarding sexual violence only rely on the provisions in Law No. 12 of 2022, Law No. 23 of 2004, the Criminal Code, and others, and as positive law is very dependent on aspects of law enforcement. Therefore, law enforcement officials must truly uphold the law and justice.